Variability of Labrador Sea Water transported through Flemish Pass during 1993–2013. Issue 8 (7th August 2015) - Schneider, Linn; Kieke, Dagmar; Jochumsen, Kerstin; Colbourne, Eugene; Yashayaev, Igor; Steinfeldt, Reiner; Varotsou, Eirini; Serra, Nuno; Rhein, Monika
Abstract Flemish Pass, located at the western subpolar margin, is a passage (sill depth 1200 m) that is constrained by the Grand Banks and the underwater plateau Flemish Cap. In addition to the Deep Western Boundary Current (DWBC) pathway offshore of Flemish Cap, Flemish Pass represents another southward transport pathway for two modes of Labrador Sea Water (LSW), the lightest component of North Atlantic Deep Water carried with the DWBC. This pathway avoids potential stirring regions east of Flemish Cap and deflection into the interior North Atlantic. Ship‐based velocity measurements between 2009 and 2013 at 47°N in Flemish Pass and in the DWBC east of Flemish Cap revealed a considerable southward transport of Upper LSW through Flemish Pass (15–27%, −1.0 to −1.5 Sv). About 98% of the denser Deep LSW were carried around Flemish Cap as Flemish Pass is too shallow for considerable transport of Deep LSW. Hydrographic time series from ship‐based measurements show a significant warming of 0.3°C/decade and a salinification of 0.03/decade of the Upper LSW in Flemish Pass between 1993 and 2013. Almost identical trends were found for the evolution in the Labrador Sea and in the DWBC east of Flemish Cap. This indicates that the long‐term hydrographic variability of Upper LSW in Flemish Pass as well as in the DWBC at 47°N is dominated by changes in the Labrador Sea, which are advected southward. Fifty years of numerical ocean model simulations in Flemish Pass suggest that these trends are part of a multidecadal cycle.